67 Impact of weight reduction on ablation outcomes in obese patients with atrial fibrillation. (17th July 2020) - Ding, Wern Yew; Chin, Shui Hao; Javed, Saad; Snowdon, Richard; Lip, Gregory; Gupta, Dhiraj
Abstract : Introduction: Obesity can adversely impact efficacy and safety of AF ablation. NHS England have recently proposed restricting ablation in obese AF patients to those who demonstrate >10% reduction in body weight. The feasibility of this degree of weight reduction in a tertiary NHS AF clinic, and its impact on efficacy and safety of AF ablation has not been reported. Methods: Consecutive AF patients with BMI>30 seen in an arrhythmia clinic were given advice to follow the 5:2 diet while on the waiting list for AF ablation. The diet involved calorie restriction to <600kCal/ day for 2 days a week, with no restrictions on the other 5 days. Patients were asked to maintain a daily weight diary. The outcomes assessed were weight loss achieved, and the recurrence of AF or atrial tachycardia following ablation. Results: 58 patients (mean age was 65.2 [±9.7] years, 50% males, 64% persistent AF) with a mean baseline weight of 109.1 (±16.8) kgs, BMI of 36.7 (±4.1) were prescribed the 5:2 diet. Following a median of 5.3 (IQR 1.7-15.1) months, a mean weight loss of 8.1 (±7.5) kg was observed prior to AF ablation, p<0.001 compared to baseline. Weight loss of >10%, 3-10% and <3% was observed in 16 (27.6%), 26 (44.8%), and 16 (27.6%) patients respectively, with weight loss of 17.9± 5.4 kgs, 6.8 ± 1.9 kgs, and 0.4 ± 2.8 kgs (P<0.001). Two procedural complications (pulmonary oedema) occurred in the entire cohort - both in group 3 (P=0.15). Over a mean follow up period of 17.3 (±13.7) months, 38/58 (65.3%) were free of AF/AT recurrence; no differences were observed between the groups, p=0.095 (Figure 1 ). Conclusions: Weight loss of >3% body weight can be achieved in the majority of patients seen in a tertiary AF clinic with a simple dietary advice, although weight reduction of greater than 10% is seen in only a minority. Modern AF ablation practice results in encouraging procedural safety as well as medium-term arrhythmia free survival rates in this traditionally difficult population, with no influence observed in our cohort of significant weight reduction. Whether this is because of advanced arrhythmia substrate by the time patients are referred for ablation is unclear. Conflict of Interest: None